Strategi Masyarakat Lokal dan Pedagang Dalam Menciptakan Kenyamanan Bagi Wisatawan - Putra, Ahmad; Rosdialena, Rosdialena; Prasetya, Bima; Ahmad, Rapi; Jelisae, Sri Kendiyol; Wardiman, Jery (Journal of Government Science Studies, 2024)
This research was motivated by the large number of reports from tourists regarding the rampant acts of extortion and disrespectful attitudes carried out by local residents who work as parking attendants, traders, and so on. This became increasingly serious when this discomfort surfaced on social media and went viral, resulting in tourists thinking twice about visiting Carocok Beach in Pesisir Selatan Regency, West Sumatra Province. If this is not addressed seriously, the impact will be felt by the regional government, local communities and traders, of course. However, efforts have been made to create comfort for tourists visiting Carokok Beach. This research uses qualitative methods accompanied by direct observations and interviews with parties who are considered capable of answering the problems in this paper. The results of this research show that: first, local people always try to be friendly towards tourists who visit Carocok Pesisir Selatan Beach, second, local people and local youth organizations investigate parties who commit extortion against tourists, third, local people maintain cleanliness tourist environment, fourth, do not increase car and motorbike parking fees arbitrarily, fifth, urge traders to be polite to tourists who shop, sixth, do not increase merchandise prices beyond the limit, seventh, ensure security for tourists by preparing security forces both from the Government and from the local community.